2021
DOI: 10.1021/acs.analchem.1c04120
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-Resolved Electrochemiluminescence Sensor Based on the Surface Plasmon Coupling Effect of a Au Nanotriangle-Patterned Structure

Abstract: This work focused on the construction of a nanomaterial-patterned structure for high-resolved ECL signal modulation. Due to the surface coupling effect, the different shapes and distribution states of surface plasmonic nanomaterials not only affect the luminescence intensity enhancement but also decide the electrochemiluminescence (ECL) polarization characteristics. Herein, tin disulfide quantum dots were synthesized via a solvothermal method as ECL emitters. Compared with other nanostructures, Au nanotriangle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Surface plasmon coupling can also confer unusual properties to ECL 214 emission as exemplified with Au nano-triangles. 215 In this very recent report, these NPs were self-assembled at the electrode surface before ECL recording with SnS 2 QDs. The pattern not only provides the signal enhancement but also generates an anisotropic circular polarization.…”
Section: Ecl Of Semiconductor Quantum Dotsmentioning
confidence: 99%
“…Surface plasmon coupling can also confer unusual properties to ECL 214 emission as exemplified with Au nano-triangles. 215 In this very recent report, these NPs were self-assembled at the electrode surface before ECL recording with SnS 2 QDs. The pattern not only provides the signal enhancement but also generates an anisotropic circular polarization.…”
Section: Ecl Of Semiconductor Quantum Dotsmentioning
confidence: 99%
“…[262][263][264] For improved sensitivity highly efficient emitters with high ECL intensity are required. So far various materials such as QDs, metal nanostructures, metal halide perovskites, carbon-based nanomaterials, MOFs [265][266][267][268][269][270] and so on have been used as efficient ECL carriers. Especially COFs can remarkably enhance loading amount of ECL luminophores and promote the excitation of external and internal ECL emitters to produce strong ECL luminescence.…”
Section: Sensing Mechanisms Of Cofs-based Electrochemical Sensorsmentioning
confidence: 99%
“…13,14 In addition, the SPC effect has been studied in the ECL sensing developments with plasmonic nanostructures. 15,16 Among a large variety of plasmonic metal nanoparticle aggregates, heterodimers are promising as emerging unique nanostructures, which consist of two closely spaced adjacent NPs with asymmetric sizes or compositions. 17,18 Plasmonic heterodimers not only possess the functions of their different nanodomains but also generate novel characteristics, such as catalytic, optical, and magnetic properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…LSPR is the collective excitation of free electrons of metal nanoparticles (NPs) in response to incident light, which can be tuned by modifying the size, geometry, chemical composition, and surrounding dielectric environment of metal NPs . In recent years, explorations have revealed that metal nanoparticle aggregates with narrow gap distances allow individual LSPRs to hybridize with each other, generating high-intensity electromagnetic hot spots in the gap region, resulting in the surface plasmon coupling (SPC) effect. , In addition, the SPC effect has been studied in the ECL sensing developments with plasmonic nanostructures. , …”
Section: Introductionmentioning
confidence: 99%